Meet me by the fountain : an inside history of the mall - Lange, Alexandra (Bloomsbury Publishing, 2022)
"Few places have been as nostalgized, or as maligned, as malls. Since their birth in the 1950s, they have loomed large as temples of commerce, the agora of the suburbs. In their prime, they proved a powerful draw for creative thinkers such as Joan Didion, Ray Bradbury, and George Romero, who understood the mall's appeal as both critics and consumers. Yet today, amid the aftershocks of financial crises and a global pandemic, as well as the rise of online retail, the dystopian husk of an abandoned shopping center has become one of our era's defining images. Conventional wisdom holds that the mall is dead. But what was the mall, really? And have rumors of its demise been greatly exaggerated? In her acclaimed The Design of Childhood, Alexandra Lange uncovered the histories of toys, classrooms, and playgrounds. She now turns her sharp eye to another subject we only think we know. She chronicles postwar architects' and merchants' invention of the mall, revealing how the design of these marketplaces played an integral role in their cultural ascent. In Lange's perceptive account, the mall becomes newly strange and rich with contradiction: Malls are environments of both freedom and exclusion--of consumerism, but also of community. Meet Me by the Fountain is a highly entertaining and evocative promenade through the mall's story of rise, fall, and ongoing reinvention, for readers of any generation"--